Channel Stuffing with Short-Term Interest in Market Value - Lai, Guoming; Debo, Laurens; Nan, Lin (Management Science, 2011)
We study how a manager's short-term interest in the firm's market value may motivate channel stuffing: shipping excess inventory to the downstream channel. Channel stuffing allows a manager to report sales in excess of demand in order to influence investors' valuation of the firm. We apply an inventory model that highlights the potential role of inventory in the manager's channel stuffing and the investors' valuation strategies. Sales in our model are constrained by available inventory. Our model yields a semiseparating and semipooling equilibrium contingent on the initial inventory level: When the demand is lower than a threshold that depends on and is below the initial inventory level, the manager pads sales by a part of the excess inventory and releases the inflated sales report. The investors “correct” the reported sales and are able to infer perfectly the firm's value. When the demand reaches or exceeds this threshold, the manager pads any excess inventory to the sales and reports the initial inventory is sold out, which censors large demand realizations. Then the investors only infer the real demand is no less than the threshold and value the firm accordingly by expectation. Channel stuffing can influence the inventory decision, too. We find both over- and underinvestment in the initial inventory can arise in our model. We discuss empirical and managerial implications of our findings. This paper was accepted by Paul H. Zipkin, operations and supply chain management.